2021
DOI: 10.5038/1936-4660.14.1.1373
|View full text |Cite
|
Sign up to set email alerts
|

Course Design and Academic Outcomes in Quantitative Literacy After Eliminating Required Remediation

Abstract: In Fall 2018, remedial mathematics courses were eliminated from the 23-campus California State University system under Executive Order 1110. Incoming first-year students were placed into college credit-bearing mathematics courses with options for corequisite support. This study examines the academic outcomes for students at California State University Monterey Bay in a college credit level quantitative literacy (QL) mathematics course with optional corequisite support during the 2018-2019 academic year. Taken … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…However, the low value of the coefficient of determination (R 2 =10.30%) suggests that while the independent variable (grade) correlates with the dependent variable (QLR scores), the grade does not explain much of the variability in the dependent variable. This is consistent with the findings of Clinkenbeard (2021), who found that among several variables used as predictors of students' grade in a college QL course, only the High School Grade Point Average (GPA) emerged as a significant predictor but accounting only to about 13% of the explained variability.…”
Section: 10supporting
confidence: 90%
“…However, the low value of the coefficient of determination (R 2 =10.30%) suggests that while the independent variable (grade) correlates with the dependent variable (QLR scores), the grade does not explain much of the variability in the dependent variable. This is consistent with the findings of Clinkenbeard (2021), who found that among several variables used as predictors of students' grade in a college QL course, only the High School Grade Point Average (GPA) emerged as a significant predictor but accounting only to about 13% of the explained variability.…”
Section: 10supporting
confidence: 90%
“…Students involved in the reform were allowed to take developmental mathematics coursework to remediate known or perceived mathematics deficiencies; however, it was not mandated. Though sometimes incorporated into other placement mechanisms, self-selection or directed self-placement, as a student placement criterion, has gained traction in the spirit of student empowerment and participation in the educational process (Mokher et al, 2021;Clinkenbeard, 2021;Minsu Kim et al, 2018). A model used uniquely in the University System of Georgia (USG) is not included in the following table.…”
Section: Student Placement Criteria For Corequisite Mathematics Coursesmentioning
confidence: 99%
“…Corequisite mathematics courses may address the mathematics content traditionally taught in stand-alone dev-ed mathematics courses Wakefield, 2020;Finder-Atkins et al, 2017), or they may be designed to provide just-in-time academic support aligned to the introductory, college-level mathematics course, commonly called the target mathematics course when aligned to corequisite mathematics remediation. Target mathematics courses span multiple pathways, including quantitative reasoning courses (Clinkenbeard, 2021), statistics (Douglas et al, 2022), college algebra (Buckles et al, 2019), precalculus (Goyer et al, 2021), and calculus (Hancock et al, 2021). Aside from the general definition of a corequisite mathematics course noted in the Introduction section and widely agreed upon in the reviewed articles, the authors of this literature review found some common design characteristics across corequisite mathematics models, including faculty experience teaching corequisite mathematics courses, use of online, self-paced curricular materials, use of non-standard pedagogical practices, and incorporation of student success skills (e.g., selfregulation, soft skills).…”
Section: Design Of Corequisite Mathematics Modelmentioning
confidence: 99%